G565(P) Recognition of childhood overweight and obesity in general paediatric outpatients. (May 2019) - Fernando, A; Cifelli, P
Abstract : Childhood obesity is a rapidly growing clinical concern: current national statistics estimate 1 in 5 children are overweight or obese when they start primary school, rising to 1 in 3 by secondary school. The National Institute of Clinical Excellence (NICE) advises tailored intervention for children with a Body Mass Index (BMI)>91 stcentile and the assessment of co-morbidities for those >98 thcentile. This should be the responsibility of every General Paediatrician, at every clinical encounter. Aim: To estimate the prevalence of childhood overweight and obesity among children attending General Paediatric Outpatients in a District General Hospital and to assess the adequacy of the clinical service provided to them. Method: For 1 week in February 2018 outgoing General Paediatric Outpatient letters were reviewed for patient height, weight and BMI. The initial sample included 46 children, but the 8 children not brought, were excluded from final analysis, leaving 38 children, aged 3 months-16 years (average age 6 years 7 months). Children with a BMI centile defined as overweight (>91 stcentile), clinically obese (>98 thcentile) or severely obese (>99.6 thcentile) were identified, and letters analysed for clinician acknowledgement, discussion and recommendations. Results: 92.1% of children had height and weight documented, but only 26.3% had BMI calculated in clinic. Following data analysis, 21% of the cohort (8 children) were found to be overweight or obese (7.9% overweight, 7.9% clinically obese, 5.3% severely obese). Only 2 children, both clinically obese, had their weight recognised, received referrals to obesity services, and had an investigation of co-morbidities. One of these children had presented with fatty liver, making obesity difficult to overlook. Conclusion: Our pilot survey indicates a poor acknowledgement of overweight and obesity. Sporadic BMI calculation underestimates the problem, and clinicians are reluctant to discuss obesity in general clinics. Recommendations include clinic support staff writing a BMI prompt alongside height and weight, local education sessions on BMI centile charts, relevant NICE guidelines and available local obesity services. We aim to re-examine our practice following these interventions, and ultimately to extend obesity awareness throughout all Paediatric clinical areas.